Developing English Vocabulary Mastery of Students at SMPIT Ibnu Sina Makassar through Word Card Games - Muhayyang, Maemuna; Asriati, Asriati; G, Hasriani (Celebes Journal of Language Studies, 2023)
This study is to describe two main points, namely (1) the development of English vocabulary mastery of 7th-grade students of SMPIT Ibnu Sina, Makassar using word card games, and (2) the aspects of vocabulary that hinder their English vocabulary development. Pre-experimental research method with pre and post-test design was used to quantitatively describe the impact of the treatment given through the use of word card games in developing students' vocabulary mastery comprising three aspects, namely (1)vocabulary forms in spelling and pronunciation, (2) denotative meaning of vocabulary, and (3) vocabulary usage focusing on the use of Present and Past Tense sentence patterns both in oral and written forms and the hindering aspects of their vocabulary mastery development which are then described qualitatively. The grade 7 students of SMPIT Ibnu Sina, Makassar totalling 28 students were the population of this study using the census sampling technique. To collect data, a vocabulary test was administered in three forms of questions, namely (1) spelling and pronunciation, (2) matching for vocabulary meaning, and (3) multiple choice and making simple sentences. The results showed that (1) the word cards could develop the English vocabulary mastery of students in terms of vocabulary form, vocabulary meaning, and vocabulary use empirically indicated by the mean score of pre-tests as 58.13 taken into an average category and post-tests is 79.72 classified into a good category and (2) the aspect that hinders students' vocabulary mastery is pronunciation and sentence construction. These findings are simply considered that word card games can be implemented to bridge the development of students’ vocabulary mastery coming along with teaching English structures.